A Majority of Family Physicians Use a Hospitalist Service When Their Patients Require Inpatient Care - Douglas Ivins; Brenna Blackburn; Lars E. Peterson; Warren P. Newton; James C. Puffer (SAGE Publishing, 2015)
Background: The hospitalist movement in the United States has risen in prominence over the past 2 decades with more physicians practicing as hospitalists. Our objective was to examine different strategies used by family physicians when their patients require inpatient care. Methods: Secondary analysis of a cross-sectional survey of physicians accessing the American Board of Family Medicine Web site in 2011 and the 2011 Area Resource File. Logistic regression assessed for associations between using hospitalists, managing inpatients personally, or with a group partner, and then comparing and contrasting these physicians with health care market characteristics. Results: A total of 3857 physicians had data on practice characteristics and could be geocoded to their county of residence. Compared with other physicians meeting inclusion criteria in the American Board of Family Medicine database, our sample was slightly older and more likely to be female. In all, 54% of respondents reported using hospitalist services while 18% reported managing hospitalized patients themselves. Respondents more likely to use hospitalist services were female and resided in urban areas. However, one third of these physicians living in isolated rural areas reported using hospitalist services. Respondents more likely to personally manage their patients in the hospital were more likely to be male and an international medical graduate. The likelihood of using hospitalist services increased with higher availability of hospitalist services. Conclusions: Overall, a majority of family physicians are using hospitalist services. Family physicians seem more likely to use hospitalist services when they are available which may lead to fragmentation of care.